Benzylthiouracil-Induced Glomerulonephritis - Sihem Trimeche Ajmi; Rim Braham; Sarra Toumi; Molka Chadli Chaieb; Amel Maaroufi; Koussay Ach; Larbi Chaieb (Case Reports in Medicine)
Vasculitis is a rare complication of antithyroid drugs (ATDs). It was first described with Propylthiouracil (PTU). We report a new case of antineutrophil cytoplasmic antibody (ANCA) vasculitis with glomerulonephritis induced by Benzylthiouracile (BTU). A 50-year-old man with Graves disease treated with BTU developed general malaise and haematuria without skin rash or respiratory involvement. Laboratory data revealed acute renal failure with proteinuria and haematuria. An indirect immunofluorescence test for ANCA was positive, showing a perinuclear pattern with specificity antimyeloperoxidase (MPO). A renal biopsy was performed and revealed pauci-immune extracapillary glomerular nephropathy and necrotic vasculitis lesions. Based on these findings we concluded to the diagnosis of rapidly progressive glomerulonephritis associated with ANCA induced by BTU therapy. The drug was therefore discontinued and the patient was treated with steroids and immunosuppressive treatment during 3 months. Renal failure, proteinuria and haematuria significantly improved within 2 months. However, P-ANCA remained positive until 10 months after drug withdrawal. Thyroid function was kept within normal range using iodine solution. We demonstrated clearly that BTU may induce severe forms of vasculitis with glomerulonephritis. Thus, the ANCA must be measured when confronted to systemic manifestation during treatment.